2017
DOI: 10.1080/19390211.2017.1330301
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Citrus Fruit Polyphenols Against Hepatic Dysfunctions: A Review

Abstract: Alcoholic liver diseases and virus-induced hepatic dysfunctions are prevalent in western countries. Evidence also suggests that hyperglycemia and insulin resistance are key players in the development of hepatic diseases and their complications. Since the comorbid diseases like obesity, diabetes and vascular dysfunctions primarily affect liver, the modern therapies against other hepatic dysfunctions are becoming a major challenge to treat. In addition to these, polypharmacy and adverse drug reactions (ADRs) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…OSD is associated with increased levels of MDA, iNOS, and ROS and decreased levels of GSH‐Px and SOD. [ 23,52‐53 ] In this study, the LCP and Vc groups exhibited significantly lower levels of ROS, MDA, and iNOS and significantly higher levels of antioxidants, such as SOD and GSH‐Px than the MG group. There were no significant differences in the levels of ROS, MDA, iNOS, SOD, and GSH‐Px between the Vc or LCP and NC groups.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…OSD is associated with increased levels of MDA, iNOS, and ROS and decreased levels of GSH‐Px and SOD. [ 23,52‐53 ] In this study, the LCP and Vc groups exhibited significantly lower levels of ROS, MDA, and iNOS and significantly higher levels of antioxidants, such as SOD and GSH‐Px than the MG group. There were no significant differences in the levels of ROS, MDA, iNOS, SOD, and GSH‐Px between the Vc or LCP and NC groups.…”
Section: Discussionmentioning
confidence: 61%
“…[ 22 ] OSD is a key factor affecting the development of liver diseases and complications. One study reported that polyphenols contribute to liver health by reducing the level of inflammatory cytokines, activating the Nrf2 pathway, inhibiting the generation of free radicals, [ 23 ] and ameliorating LPS‐induced liver injury by regulating the intestinal homeostasis and increasing the abundance of Akkermansia and Clostridium . [ 24 ] Moreover, LPS can bind to the TLR4 of the TLR family to activate the mitogen‐activated protein kinase (MAPK) signaling pathway and exacerbate liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (3,3′,4′,5,7-pentahydroxyflavone) is one of the most common dietary flavonols present in the apple, onion, black or green tea, herbal medicine, and red wine [ 69 , 70 ]. Many studies have reported that quercetin exerts a beneficial role in non-alcoholic fatty liver disease (NAFLD), ALD, and diabetes mechanically by regulating the expression of lipid-metabolism-related genes and the secretion of inflammatory mediators [ 69 , 70 , 71 , 72 , 73 ]. Quercetin blocked autophagy suppression induced by ethanol.…”
Section: Bioactive Compounds Ameliorate Ald Via Multiple Pathwaysmentioning
confidence: 99%
“…Having any kind of inflammatory response in a biological system explains the ultimate preventive and protective mechanisms that keep the body safe and active in response to harmful stimuli. Inflammatory defenses can be initiated either against live organisms or dead components [ 20 , 21 ]. However, a disease may be initiated when an inflammatory cascade system persists for a longer time in a particular tissue or an organ.…”
Section: Immunity Inflammation and Autoimmune Diseasesmentioning
confidence: 99%
“…Immunity, inflammation and inflammatory diseases have been recognized since the beginning of recorded medical knowledge and practice. Inflammation is a process of complex biological representation to cellular damage caused either by necrosis or infection or lysis, in which the feedback system by the immune system endeavors to neutralize or eliminate injurious stimuli and starts wound healing and regenerative processes [ 21 , 25 ]. For instance, interleukin-6, a key tumor-pro- moting inflammatory marker generated by innate immunity, signals, at least, three regeneration-promoting transcription factors such as Notch protein, yes-associated protein 1 (YAP), and Signal transducer and activator of transcription 3 (STAT3), which are also involved in stem cell activation in both autocrine and paracrine systems.…”
Section: Is Inflammation Good or Bad?mentioning
confidence: 99%